An academic knowledge management model: Multiple case studies in Peruvian Universities - Morgan Rozas, Milagros (2017)
Proceedings of the European Conference on Knowledge Management, ECKMVolume 2, 2017, Pages 730-74118th European Conference on Knowledge Management, ECKM 2017; International University of CataloniaBarcelona; Spain; 7 September 2017 through 8 September 2017.